Heightened generalized conditioned fear and avoidance in women and underlying psychological processes. (April 2022) - Cooper, Samuel E.; Hunt, Christopher; Ross, Jack P.; Hartnell, Melissa P.; Lissek, Shmuel
Abstract: Heightened generalization of conditioned fear and avoidance to safe stimuli resembling threat is a key feature of pathological anxiety and might contribute to the increased prevalence of anxiety-related disorders among women. Though animal studies have documented over-generalized fear in female versus male rodents, analogous work in humans is sparse, and no studies to date have examined gender differences in generalized avoidance. We addressed this gap by testing 170 self-identified women ( n = 85) and men ( n = 85) using a video game-based task assessing generalized Pavlovian fear (perceived threat, fear-potentiated startle) and generalized instrumental avoidance. Instrumental measures of generalization reflected maladaptive avoidance by virtue of being unnecessary to secure safety and incurring a cost of losing the game in which the task is embedded. Women displayed increases in both Pavlovian generalization of perceived threat and maladaptive generalized avoidance. Additionally, decreased motivation to win the game among women mediated the effect of gender on generalized avoidance, and generalized perceived risk and tendencies toward experiential avoidance positively predicted generalized avoidance in women but not men. Overall, findings implicate the undue spread of fear and avoidance to safe stimuli resembling danger among women as a candidate mechanism for differential rates of clinical anxiety across the genders. Highlights: Women show heightened generalization of conditioned fear and avoidance. Reduced approach motivation in women mediates their increases in generalized avoidance. Increases in generalized perceived risk are more often accompanied by maladaptive avoidance among women. Higher experiential avoidance predicts increases in generalized avoidance in women but not men. Elevated generalization in women might contribute to their increased rates of anxiety-related disorder diagnosis.